Perancangan Media Promosi pada Auorora Studio Foto - Artika Putri Prameswari; Irdha Yunianto (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
This study focuses on the design of promotional media for Aurora Photo Studio as a response to the increasingly competitive creative industry. The research was conducted using the Research and Development (R&D) method, which involves stages of analysis, design, development, implementation, and evaluation. The results revealed several key challenges faced by the studio, including limited use of promotional media, lack of consistent visual strategies, and suboptimal utilization of social media platforms. Through the design and validation of visual media such as logos, flyers, price catalogs, and digital content for social media, this research produced promotional outputs that are both aesthetically appealing and strategically effective. The evaluation results showed positive responses from respondents, with an overall average score of 3.86, indicating that the promotional designs succeeded in enhancing brand identity and public awareness. Despite these achievements, the findings also highlight the need to strengthen elements that directly motivate purchase decisions. Overall, this research demonstrates that well-planned visual communication strategies play an essential role in supporting the growth of creative businesses and building a strong connection with target audiences.